2012
DOI: 10.1007/s10479-012-1177-3
|View full text |Cite
|
Sign up to set email alerts
|

Lean principles, practices, and impacts: a study on small and medium-sized enterprises (SMEs)

Abstract: Lean as a business strategy is used to improve quality and service, eliminate waste, reduce time and costs, and enhance overall organizational effectiveness. Heightening challenges in competition in recent years have prompted many small and medium-sized enterprises (SMEs) to adopt lean to enhance firms' competitiveness. This paper attempts to present an all-inclusive study and it examines various factors associated with the implementation of lean in SMEs in the U.S. The findings suggest that most of SMEs have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
186
1
15

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(236 citation statements)
references
References 15 publications
(11 reference statements)
4
186
1
15
Order By: Relevance
“…Moreover, the framework contains guidelines, tools and practices affirmed to be suitable for SMEs by several authors (Matt & Rauch, 2013;Zhou, 2012;Real, Pralus, Pillet & Guizzi, 2007). For these reasons, the proposed roadmap meets the criterion of "Implementable".…”
Section: Features Of the Proposed Framework Of Lean Implementation Inmentioning
confidence: 99%
“…Moreover, the framework contains guidelines, tools and practices affirmed to be suitable for SMEs by several authors (Matt & Rauch, 2013;Zhou, 2012;Real, Pralus, Pillet & Guizzi, 2007). For these reasons, the proposed roadmap meets the criterion of "Implementable".…”
Section: Features Of the Proposed Framework Of Lean Implementation Inmentioning
confidence: 99%
“…According to Aspinwall (1999, 2000) and Dora, Kumar, and Gellynck (2016), a lack of resources can act as an excuse not to improve, and the measurement of results, progress and performance is critical for implementing lean practices. Zhou (2016) found that the lack of time and budgets was high for companies with initial implementation of lean practices and Hu et al (2015) found that training was important to diffusing lean implementation. The criticality of support congruence in the initial stages of implementing lean is also plausible because employees act, or refrain from acting, based on the rewards they receive, both intrinsically and extrinsically.…”
Section: Focus On Shop-floor Activities When Starting With Leanmentioning
confidence: 99%
“…Sakakibara, Flynn, and Schroeder (1993) and Danese, Romano, and Bortolotti (2012) found no direct link between external JIT and performance, and argue that external JIT might be necessary for internal JIT rather than directly linked to performance. Saraph, George Benson, and Schroeder (1989), Motwani, Mahmoud, and Rice (1994), Aspinwall (1999, 2000), Hu et al (2015) and Zhou (2016) found that suppliers came in at a later stage, after many of the internal improvements had been accomplished. This order of improving the supply chain was replicated in our findings.…”
Section: Downstream Improvements Precede Upstream Improvementsmentioning
confidence: 99%
“… Some definitions speak about value as perceived by the customer (Arbulu et al, 2003;Eswaramoorthi et al, 2011;Arumugan et al, 2012;Zhou, 2012); value for the (end)…”
Section: The Concept Of Waste As Non-value Adding Activitymentioning
confidence: 99%